Infrapolitical passages global turmoil, narco-accumulation, and the post-sovereign state - Williams, Gareth 1963- (Fordham University Press, 2021)
This book makes a case for infrapolitics as an enactment of intellectual responsibility in the face of a tumultuous world of war and of technological value extraction on a planetary scale. Infrapolitical Passages proposes to clear a way through some of the dominant political determinations and violent symptoms of contemporary globalization. In doing so, Gareth Williams makes a case for infrapolitics as an enactment of intellectual responsibility in the face of a tumultuous world of war and of technological value extraction on a planetary scale. The book offers a theory of globalization as a gigantic, directionless crisis in humanity's symbolic organization, as well as a theory of global economic warfare as the very positing of directionlessness and, at the same time, facticity. Williams's infrapolitics stands at a distance from the biopolitical, which it understands as domination presenting itself as the production of specific forms of subjectivity in the face of the commodity. The subsequent obscuring of being signals the need to circumvent the instrumentalization of life as subordination to the metaphysics of subjectivity, representation, and politics. Infrapolitical Passages works to confront that which is unavailable in subjectivity and representation, opening a way for facticity in the age of globalization in order to make room for the infrapolitical question for existence